Senior citizens working in european companies report - Puyol Antolín, Rafael; Sagardoy, Íñigo; Alvarado, Gisella; Jiménez, Alfonso; Ardid, Beatriz; Orden, Elena; Morillo Velarde, Cristina (IE Fundation, 2021)
When we prepared the report on Senior Citizens Working in Spanish Companies (Madrid 2018), some data was included to compare our situation with that of other European countries. The comparison of the active and employed population aged 55 and over in Spain yielded unfavorable balances in relation to other EU territories, especially with the countries of the north and some of the central-west. This led us to propose a second report on Senior Citizens Working in European Companies whose objective is to find out what is being done in other countries with respect to this segment of the working population.

En 2017, un 14,17% de la población activa española estaba formada por trabajadores sénior (de más de 55 años). En Alemania, Finlandia y Suecia suponen más del 20%. Los responsables del estudio señalan que su peso va a aumentar en nuestra economía en los próximos 10 años de forma significativa. Según el estudio ‘Los trabajadores séniors en las empresas europeas” las tasas de actividad de los trabajadores seniors en España baja del 61% en la franja de edad de 55 a 59 años, hasta el 36,6 % (60-64) o 6,2% (65-59). El informe analiza también la legislación laboral relativa a los trabajadores mayores de 55 años en varios países del norte, centro y sur de Europa, así como las buenas prácticas empresariales.
Los trabajadores séniors en las empresas europeas
Keywords: Sociodemographic study;Europe;Sociodemographic report;Legislation;European companies;Demografía;Europa;Legislación;Empresa; Sociodemographic study; Europe; Sociodemographic report; Legislation; European companies; Demografía; Europa; Legislación; Empresa